Complications of Regional Anesthesia: A Comprehensive Review of Neurological Injury, Hematoma, and Infection - Bonarska, Marta; Adasik, Damian; Herjan, Katarzyna; Chmura, Katarzyna; Zimnoch, Barbara; Rendaszka, Katarzyna; Pyziołek, Marta; Kwaśniewska, Paulina; Stróżna, Małgorzata; Najbar, Joanna Monika; Kowalska, Katarzyna (Quality in Sport, 2025)
Background. Regional anesthesia is increasingly used due to its advantages over general anesthesia; however, its potential complications require careful evaluation. Aim. This review aimed to synthesize current evidence on the incidence, risk factors, and prevention of neurological injury, hematoma, and infection associated with regional anesthesia. Material and methods. Relevant peer-reviewed literature—including systematic reviews, retrospective cohorts, and randomized trials—was analyzed to provide a comprehensive overview. Results. Neurological complications, though uncommon, may persist in a subset of patients and are linked to factors such as high-pressure intrafascicular injection and inadequate needle guidance. Hematomas remain rare but are more likely in patients on anticoagulants and can result in permanent deficits if diagnosis and decompression are delayed. Infections, particularly with prolonged catheter use, present a serious risk, with higher rates in peripheral nerve blocks and pediatric populations. Conclusions. Preventive strategies include ultrasound guidance, triple safety protocols, careful antithrombotic management, and strict aseptic techniques. Recent evidence supports the efficacy of real-time pressure monitoring and prophylactic antibiotic use in reducing adverse outcomes. This review underscores the importance of patient-specific risk assessment and adherence to evolving safety protocols in minimizing complications from regional anesthesia.